PENGARUH PEMBERIAN BUAH MELON TERHADAP PENURUNAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA PENDERITA HIPERTENSI USIA 41-64 TAHUN - Nuke Melati Anindea; Ria Ambarwati; Susi Tursilowati; J Supadi (JURNAL RISET GIZI, 2019)
Background : Hypertension is a health issues that needs attention. Based on Riskesdas Data, prevalence of hypertension increased from 7,6% in 2007 to 9,5% in 2013. One of the treatments which can be done is by giving fruits that contain potassium and fiber.Objective : To determine the effect of melon fruit on the decrease systolic and diastolic blood pressure in patients with hypertension age 41-64 years.Method : This study used Quasi Experiment method with Pretest Posttest Control Group Design. The samples of study was determined by non randomized sampling technique consists of 11 treatments and 11 controls sampels.Results : there was significant difference in systolic and diastolic blood pressure between the treatment and control group (p0,05). There was no effect of giving melon fruit to decrease systolic (p=0,071) and diastolic (p=0,042) blood pressure in patient hypertension with control variable of sodium, potassium, magnesium, calcium and fiber intake.Conclusion : Consumption of melon fruit for 9 days can reduce systolic blood pressure 14.82±5.759 mmHg and diastolic of 7.64±2.292 mmHg, although statistically  insignificant